Digital Savvy Melalui Pelatihan Copywriting dan Storytelling bagi Pemuda Karang Taruna Malai V Suku Timur menuju Branding Nagari: Digital Savvy Through Copywriting and Storytelling Training for Malai V Timur Clan Karang Taruna Youth Towards Village Branding - Abdurahman, Abdurahman; Triana, Herlin; Indriyani, Vivi; Amir, Amril; Emidar, Emidar; Putri, Delsy Arma; Henanggil, Mita Domi Fella (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Nagari Malai V Suku Timur, a newly established village, faces challenges in developing its branding due to limited digital literacy and the underutilization of technology to promote local potential. This condition weakens the competitiveness of agricultural products, tourism, and local SMEs. This community service program aimed to enhance the skills of Karang Taruna youth through copywriting and storytelling training as digital communication strategies to strengthen village branding. The method applied was direct training consisting of lectures, practice, discussions, and mentoring, conducted over two days (24–25 July 2025) at the Malai V Suku Timur Village Office Hall with 15 active participants. The results revealed that participants gained a clear understanding of copywriting and storytelling and successfully applied these skills to social media content using Canva and Instagram. Evaluation through pre-tests, post-tests, and satisfaction surveys indicated highly positive responses, with improved comprehension, practical skills, and participant satisfaction. The implication of this activity is the potential empowerment of village youth to optimize digital media for branding, which is expected to contribute to sustainable development in the economic, tourism, and SME sectors.